2014
DOI: 10.1002/adma.201401906
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Surface Fatigue in a Nano‐Layered Material

Abstract: Nanoscale materials fatigue within a single 7 Å layer of a 2D nano-layered material, muscovite mica, resembles fatigue in macroscopic systems except for two remarkable properties: first, there is an Å-scale precision in the depth of the damage and second, there are sharply defined "magical" stresses, beyond yield, at which the surface remains intact regardless of the number of applications of stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The spring constants of the cantilevers were determined from measurements of the resonance frequency and were within 20% of the manufacturer’s suggested values. As in previous work 38 39 , we monitored the adhesion force to identify any changes in the tip size during the experiments. Throughout these experiments, the adhesion force was unchanged, consistent with a constant tip size and shape during these experiments.…”
Section: Methodsmentioning
confidence: 99%
“…The spring constants of the cantilevers were determined from measurements of the resonance frequency and were within 20% of the manufacturer’s suggested values. As in previous work 38 39 , we monitored the adhesion force to identify any changes in the tip size during the experiments. Throughout these experiments, the adhesion force was unchanged, consistent with a constant tip size and shape during these experiments.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] There is a great interest in the development of field emission (FE) cathodes, photodetectors and logic devices using 1D and 2D nanomaterials, such as carbon nanotubes, graphene, ZnO, LaB 6 , In 2 Se 3, MoS 2 , SnS 2 , CdS and Bi 2 S 3 . 12,14-24 Two dimensional graphene and its inorganic analogues transition metal di-chalcogenides (TMDCs) are important for planar device technology.…”
Section: Introductionmentioning
confidence: 99%
“…12,14-24 Two dimensional graphene and its inorganic analogues transition metal di-chalcogenides (TMDCs) are important for planar device technology. [1][2][3][4][5][6][7][8][9][10][11][12][13] The lead bismuth selenide (PbBi 2 Se 4 ) nanosheet, an intergrowth compound, which contains septuple layers each of approximately ~1.3 nm thick and composed of seven covalently bonded atomic planes [Se 2 -Bi-Se1-Pb-Se1-Bi-Se 2 ] [25][26][27][28][29][30] Owing to its superior electrical conductivity, narrow band gap (~0.6 eV) and high mobility of ~ 155 cm 2 V -1 s -1 at room temperature, the ultrathin PbBi 2 Se 4 has potential to be used in next generation nanoelectronic photosensitive devices. The temperature dependent electrical transport properties of PbBi 2 Se 4 nanosheets have been demonstrated in our recent work.…”
Section: Introductionmentioning
confidence: 99%
“…However, when the same recipe and the same EBL setting were tested on a silicon substrate (washed with acetone, isopropyl alcohol (IPA) and deionised (DI) water and dried with a nitrogen gun), the optical image showed that the pattern was deposited and developed successfully, with four different pattern areas with varying exposure doses (20,30,40,50 μC/cm 2 ) (see Figure 7.3). In order to solve this issue and improve the adhesion between the mica and the resist, an extra adhesion layer was deposited on the mica substrate prior to the application of the resist.…”
Section: The Problem Of the Adhesion Between The Mica And The Resist Layer Or Any Other Layermentioning
confidence: 99%